Suppression of LPS-induced inflammatory responses in macrophages infected with Leishmania - Kelly Ben L; Lapara Nicholas J (BMC, 2010)
Abstract Background Chronic inflammation activated by macrophage innate pathogen recognition receptors such as TLR4 can lead to a range of inflammatory diseases, including atherosclerosis, Crohn's disease, arthritis and cancer. Unlike many microbes, the kinetoplastid protozoan pathogen Leishmania has been shown to avoid and even actively suppress host inflammatory cytokine responses, such as LPS-induced IL-12 production. The nature and scope of Leishmania-mediated inflammatory cytokine suppression, however, is not well characterized. Advancing our knowledge of such microbe-mediated cytokine suppression may provide new avenues for therapeutic intervention in inflammatory disease. Methods We explored the kinetics of a range of cytokine and chemokine responses in primary murine macrophages stimulated with LPS in the presence versus absence of two clinically distinct species of Leishmania using sensitive multiplex cytokine analyses. To confirm that these effects were parasite-specific, we compared the effects of Leishmania uptake on LPS-induced cytokine expression with uptake of inert latex beads. Results Whilst Leishmania uptake alone did not induce significant levels of any cytokine analysed in this study, Leishmania uptake in the presence of LPS caused parasite-specific suppression of certain LPS-induced pro-inflammatory cytokines, including IL-12, IL-17 and IL-6. Interestingly, L. amazonensis was generally more suppressive than L. major. We also found that other LPS-induced proinflammatory cytokines, such as IL-1α, TNF-α and the chemokines MIP-1α and MCP-1 and also the anti-inflammatory cytokine IL-10, were augmented during Leishmania uptake, in a parasite-specific manner. Conclusions During uptake by macrophages, Leishmania evades the activation of a broad range of cytokines and chemokines. Further, in the presence of a strong inflammatory stimulus, Leishmania suppresses certain proinflammatory cytokine responses in a parasite-specific manner, however it augments the production of other proinflammatory cytokines. Our findings highlight the complexity of inflammatory cytokine signalling regulation in the context of the macrophage and Leishmania interaction and confirm the utility of the Leishmania/macrophage infection model as an experimental system for further studies of inflammatory regulation. Such studies may advance the development of therapies against inflammatory disease.